Integrating simulation, role-play, and technology in physiotherapy education: A narrative review on teaching methods for patient education - Ida Bagus Amertha Putra Manuaba; Made Violin Weda Yani; Anak Agung Bagus Putra Indrakusuma; Ketut Liana Arya Dewi; Putri Ayu Wulandari; Ngurah Arya T. Mahadipaka K.A; Ni Luh Ayu Sasmitha; I Gede Putu Supadmanaba (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Physiotherapists play a crucial role in patient education, as effective communication and educational strategies directly influence treatment adherence, functional outcomes, patient satisfaction, and trust in healthcare services. The increasing global burden of musculoskeletal and neurological disorders has intensified the demand for physiotherapy services, emphasizing the need for graduates who are not only clinically competent but also proficient in patient-centered education. This narrative review aims to synthesize evidence from 2015 to 2025 regarding the integration of simulation, role-play, and educational technology in physiotherapy education, with a particular focus on teaching methods that enhance patient education competencies. Relevant peer-reviewed literature was identified from major academic databases, including PubMed, Scopus, and Google Scholar, and analyzed thematically to examine educational outcomes related to communication skills, learner engagement, confidence, empathy, and clinical preparedness. The findings indicate that simulation-based learning and structured role-play provide safe and experiential environments for students to practice patient communication and education, while technology-enhanced approaches such as virtual simulations and digital learning platforms offer scalable and flexible learning opportunities. Collectively, these methods demonstrate consistent benefits in improving students’ ability to deliver clear, structured, and empathetic patient education, thereby supporting readiness for clinical practice. Integrating simulation, role-play, and technology within physiotherapy curricula represents a strategic approach to strengthening patient education competencies and preparing graduates to deliver high-quality, patient-centered, and trusted physiotherapy care in response to contemporary healthcare demands.